Pengolahan Bakso Berbahan Jantung Pisang Pada Kelompok Jalapagos Desa Buon Mandiri Kabupaten Banggai Sulawesi Tengah - Lamusu, Darni; Chaniago, Ramadhani; Ode, Haruni; Lasamadi, Rahman Dani (Society : Jurnal Pengabdian Masyarakat, 2022)
Banana hearts are usually cut so as not to inhibit fruit growth and prevent disease in banana plants, so they are considered waste. Actually the banana heart can be processed into beef jerky or meatballs which are rich in fiber. Implementation of activities includes observation, preparation, implementation and evaluation. The results of the implementation of training in making banana heart meatballs can increase knowledge and skills of mothers who are members of the Jalapagos group, about the potential of banana plants, namely banana flowers, which can be a new source of income so that they can improve the welfare of the community in Buon Mandiri village, Banggai district, Central Sulawesi. Then the community really expects the training activities as it has been implemented to continue to be carried out.